Examining Predisposing Factors and Program Performance Indicators Associated With Program Completion: A Comparison of Opioid and Non-Opioid-Preferring Participants in Drug Court. (September 2020) - Shannon, Lisa M.; Jones, Afton Jackson; Newell, Jennifer; Nichols, Elizabeth
Opioid use and abuse, as well as criminal justice involvement, have increased dramatically in the past two decades. Drug court is a community-based rehabilitation program for individuals with substance abuse issues involved in the criminal justice system. Given unique treatment needs associated with opioids, the current study examined predisposing factors and program performance indicators associated with drug court completion based on individuals' opioid preference. Secondary data (i.e., participant assessment and drug court Management Information System) as well as conviction information from a statewide database were examined for a sample of drug court participants ( N = 534). Data analyses compared opioid-preferring ( n = 267) and non-opioid-preferring ( n = 267) program participants. For non-opioid-preferring participants, a combination of predisposing characteristics, including both social/demographic characteristics and substance use (i.e., education, drug court site, lifetime benzodiazepine use), as well as program performance indicators (i.e., number of days in drug court, number of positive drug tests, and sanctions/therapeutic responses) influenced drug court completion. For opioid-preferring participants, only program performance indicators emerged as important for program completion, specifically number of days in drug court, number of positive drug tests, and sanctions/therapeutic responses. Findings for non-opioid-preferring participants are consistent with past research, suggesting that individual predisposing characteristics and program performance indicators are influential on program completion. However, findings suggesting that only program performance indicators are influential for opioid-preferring participants adds a unique contribution to the literature. This information may help provide more individualized program planning and ultimately more programmatic success.